(untitled) (Bioscience Journal, 2017)
The ability of bryophytes to tolerate salt is determined by a number of biochemical routes, whereas the salt ends up driving the activation of adaptive responses to tolerate this adverse condition. Salinity is the main limiting environmental factor under plant development, and is caused by excess salt ions in the environment, mainly Na + and Cl-. The optimal growth of plants in saline environment is obtained in concentrations of 50% of NaCl. Due to these findings, the importance of the study of the effect of salinity on the germination of plants, in this case in Funaria hygrometrica Hedw., is noticed.